(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This thesis describes the issues of improving the methodology of establishing national standards of goodwell in accounting based on international standards and the use of new methods in accounting of goodwell